Integration and Control of Distributed Renewable Energy Resources - Hamidreza Nazaripouya (Clean Technologies, 2022)
The increase in the population growth rate and the motivation to overcome issues such as environmental concerns and air pollution have made distributed renewable energy resources (DRER) the most popular option for providing the required energy [...]